The Influence Of Internet Banking, Mobile Banking, And Atm Usage On Financial Management Among Customers Of Bank Muamalat Kcp Binjai - Muhammad Fahri Siregar; Tia Novira Sucipto; Heriyati Chrisna (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of using Internet Banking, Mobile Banking, and ATM on the financial management of customers of PT. Bank Muamalat Indonesia Tbk KCP Binjai. The research uses a quantitative approach with a survey method. The research sample consisted of 40 customers selected by saturated sampling technique. Data were collected through questionnaires and analyzed by multiple linear regression. The results showed that Internet Banking and Mobile Banking have a positive and significant effect on financial management, while ATM has no significant effect. Simultaneously, the three banking services contribute 70.7% to financial management. The implications of this research are expected to be input for Bank Muamalat in optimizing digital services to support customer financial management.